The Application of Game Theory in Engineering Management: Competitive and Cooperative Strategies - Eslami, Sara; Naderi, Mahmoud (Management Strategies and Engineering Sciences, 2021)
The application of game theory in engineering management has emerged as a critical tool for enhancing decision-making in complex and competitive environments. This narrative review examines the use of both competitive and cooperative game theory strategies within engineering management, synthesizing findings from the literature to identify key trends, gaps, and practical implications. The review reveals a growing interest in the application of competitive strategies, particularly in bidding and resource allocation scenarios, while also highlighting the increasing importance of cooperative strategies in fostering collaboration in large-scale engineering projects. However, the literature is found to be limited by a predominance of theoretical models over empirical validation and a lack of focus on ethical considerations. The review concludes by offering practical recommendations for engineering managers, emphasizing the need for empirical validation of game theory models, exploration of cooperative strategies, and attention to ethical implications in decision-making.